Art in the Anthropocene: Encounters Among Aesthetics, Politics, Environments and Epistemologies - Davis, Heather (Critical Climate Change, 2015)
Taking as its premise that the proposed geologic epoch of the Anthropocene is necessarily an aesthetic event, this book explores the relationship between contemporary art and knowledge production in an era of ecological crisis, with contributions from artists, curators, theorists and activists. Contributors include Amy Balkin, Ursula Biemann, Amanda Boetzkes, Lindsay Bremner, Joshua Clover & Juliana Spahr, Heather Davis, Sara Dean, Elizabeth Ellsworth & Jamie Kruse (smudge studio), Irmgard Emmelhainz, Anselm Franke, Peter Galison, Fabien Giraud & Ida Soulard, Laurent Gutierrez & Valérie Portefaix (MAP Office), Terike Haapoja & Laura Gustafsson, Laura Hall, Ilana Halperin, Donna Haraway & Martha Kenney, Ho Tzu Nyen, Bruno Latour, Jeffrey Malecki, Mary Mattingly, Mixrice (Cho Jieun & Yang Chulmo), Natasha Myers, Jean-Luc Nancy & John Paul Ricco, Vincent Normand, Richard Pell & Emily Kutil, Tomás Saraceno, Sasha Engelmann & Bronislaw Szerszynski, Ada Smailbegovic, Karolina Sobecka, Zoe Todd, Richard Streitmatter-Tran & Vi Le, Anna-Sophie Springer, Sylvère Lotringer, Peter Sloterdijk, Etienne Turpin, Pinar Yoldas, and Una Chaudhuri, Fritz Ertl, Oliver Kellhammer & Marina Zurkow.